A generalized approach to anti-sway control for shipboard cranes. (1st February 2021) - Martin, Iain A.; Irani, Rishad A.
Highlights: A generalized trajectory modification strategy is proposed for anti-sway control. The modifier is applied to both a shipboard gantry and knuckle boom crane. The knuckle boom crane includes internal actuator dynamics and inertia. PID and sliding mode controllers are developed to track the modified trajectory. With the trajectory modifier the tracking RMSE is improved by up to 84%. Abstract: Payload sway for shipboard cranes represents a significant safety concern for deck personnel. In this paper, a generalized trajectory modification strategy is presented that can be applied to a variety of different types of shipboard crane to allow the payload to maintain its desired position with respect to the ship deck in the presence of six degree of freedom (DOF) ship motion, and therefore appear stationary to deck personnel. Initially developed for a five DOF shipboard gantry crane, both a de facto proportional-integral-derivative (PID) controller and a sliding mode controller (SMC) are shown in simulation to be successful at tracking the modified trajectory. The PID controller shows a 64 % reduction in the root-mean-square-error (RMSE) between the desired and actual payload positions with the addition of the trajectory modifier, and the SMC shows a 74 % reduction. The ship is actuated with six degrees of freedom in the simulations; however, the trajectory modification anti-sway control system only requires the measurement of the ship's roll and pitch angles. The trajectory modifier is then applied to a six-DOF shipboard knuckle boom crane, with a dynamic model developed to include the mass and inertia of the actuators. The PID controller only shows a 38 % reduction in RMSE and struggles to successfully track the trajectory due to the highly nonlinear dynamics of the knuckle boom crane. The SMC controller shows an 82 % reduction in RMSE and appears capable of maintaining the desired payload position with the addition of the trajectory modifier. To further extend the dynamic model of the knuckle boom crane, first-order transfer functions are applied to govern the response of each actuator. A state-of-the-art sliding mode controller is developed to provide stable control of the system, and shows an 84 % reduction in RMSE with the addition of the trajectory modifier. The results therefore indicate that trajectory modification is highly effective at dampening payload sway for shipboard cranes, provided a suitable controller can be developed to allow the crane to accurately track the modified trajectory.